UNDERGRADUATE THESIS THE IMPLEMENTATION OF THE RIGHTS OF STUDENTS WITH DISABILITIES IN THE UNIVERSITIES IN YOGYAKARTA IN THE PERSPECTIVE OF INTERNATIONAL HUMAN RIGHTS LAW AND THE CONVENTION ON THE R - Shidqi Noer Salsa (FH 15 UMY 057, 2015)
*57 International education system in the world at the present time is a compulsory to be enjoyed by all people, since the education is the right of all human beings, including the disable persons. This system affects the development of education in Indonesia, since Indonesian education is also a part of the education system in the world which has to provide the same facilities for every individual. A lot of efforts from activists focus on education rights of disable people in Indonesia to fight for the rights of disabilities to set a proper education. This struggle is getting reinforcement by the ratification of the Convention on the Right of Persons with Disabilities (CRPD) by the Indonesian Government in 2011. This study aims to examine whether or not the universities in Yogyakarta as an education city that has hundreds of campuses becomes more inclusive in fulfilling the rights of students with disabilities. The method used in this study is a library research and field research with qualitative descriptive approach. Respondents of this study are the students of the five largest campuses in Yogyakarta. The results showed that most of the campus in Yogyakarta did not meet the disable-friendly standards.. Indeed, this is a violation of international human rights law and the local law of Indonesia, which have been enacted after the ratification of the CRPD. The study also recommends that the Indonesian government should make a legislation which specifically states that universities in Indonesia are obliged to facilitate the disables to get a good education as a â€œnormalâ€ person.